RZFS ANALISIS PENGARUH INTEGRASI SUPPLY CHAIN MANAGEMENT TERHADAP KINERJA BISNIS UMKM DI KOTA MEDAN PADA MASA COVID 19 - Rabbli Siregar; Meyra Rizky Azhary (Politeknik Negeri Jakarta, 2022)
This study develops the developing writing on Supply Chain Integration (SCI), which is how much a maker decisively teams up with its store network accomplices and cooperatively oversees intra and between hierarchical cycles of SMEs in the City of Medan during the Covid-19 time, to accomplish a consistent stream. viable and productive. items and administrations, data, cash and choices, to offer most extreme benefit to clients. Past examination has been conflicting in its discoveries on the connection among SCI and execution. We property this irregularity to the deficient meaning of SCI, specifically, the propensity to zero in on client and provider joining just, barring the significant focal connection of inner reconciliation. We concentrate on the connection between the three components of SCI, functional and business execution, from both a possibility and design point of view. In applying the possibility approach, progressive relapse was utilized to decide the effect of individual SCI aspects (clients, providers, and inside combination) and their collaborations on execution. The discoveries from the possibility and design approach show that SCI is connected with functional and business execution. Besides, the outcomes show that inward and client combination is more firmly connected with further developed execution than provider incorporation.